2013
DOI: 10.1097/mpa.0b013e3182965915
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC4 Mucin Is Observed Mainly in the Intestinal Type of Intraductal Papillary Mucinous Neoplasm of the Pancreas

Abstract: Objectives This study aimed to examine expression profile of MUC4 in intraductal papillary mucinous neoplasm of the pancreas (IPMN). Methods We performed immonohistochemistry (IHC) of MUC4 in 142 IPMNs, with evaluation of the specificity of two anti-MUC4 monoclonal antibodies (MAbs), 8G7 and 1G8, in cancer cell lines. Results MAb 8G7 showed a clear immunoreactivity, whereas MAb 1G8 did not show any immunoreactivity, in the Western blotting and IHC for human pancreatic carcinoma cell lines expressing MUC4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…27 However, head-to-head comparison of 1G8 with Mab 8G7 which recognizes human MUC4 has conclusively demonstrated that 1G8 neither recognizes human MUC4, nor exhibits staining pattern similar to human MUC4 antibody. 30, 31 A recent study using MAb 8G7 reported MUC4 overexpression (58%) in OSCC and its association with higher T classification, positive nodal metastasis, advanced tumor stage, diffuse invasion of cancer cells and bad prognosis. 29 In accordance with this report, we also observed a significant upregulation of MUC4 (68%) in HNSCC tissues compared to benign samples (P= 0.006), but contrary we did not observe any significant association of MUC4 overexpression with any clinical or pathological characteristics of patients (Figure 1 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…27 However, head-to-head comparison of 1G8 with Mab 8G7 which recognizes human MUC4 has conclusively demonstrated that 1G8 neither recognizes human MUC4, nor exhibits staining pattern similar to human MUC4 antibody. 30, 31 A recent study using MAb 8G7 reported MUC4 overexpression (58%) in OSCC and its association with higher T classification, positive nodal metastasis, advanced tumor stage, diffuse invasion of cancer cells and bad prognosis. 29 In accordance with this report, we also observed a significant upregulation of MUC4 (68%) in HNSCC tissues compared to benign samples (P= 0.006), but contrary we did not observe any significant association of MUC4 overexpression with any clinical or pathological characteristics of patients (Figure 1 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Our immunohistochemistry (IHC) studies of mucin expression profiles in pancreatic neoplasms 7,8 have shown that high expression of MUC1 is observed in PDACs and is related to a poor outcome 9 -11 ; intestinal-type IPMNs are MUC1-negative but MUC2 (intestinal secretory mucin)-positive, and may show invasive growth with de novo MUC1 expression; gastric-type IPMNs that are MUC1-negative and MUC2-negative have low malignant potential 10-12 ; de novo high MUC4 (tracheobronchial membrane mucin) expression is associated with a poor outcome in PDAC 11 ; and MUC4 expression mainly in intestinal-type IPMNs 13 . Haridas et al showed that MUC16 expression is also associated with a poor outcome in PDAC 14 and we have found an association of MUC16 expression with a poor outcome in cholangiocellular carcinoma 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that different clinical characteristics and distinct pathways to malignant progression exist among the various IPMN subtypes. Genetic alteration such as mutational status of GNAS or KRAS [ 42 44 ], as well as expression pattern of mucin [ 42 , 43 , 45 , 46 ] have been investigated. Recent meta-analysis suggested that subtype identification should be considered in future guidelines for management of IPMN, since subtypes have an impact on disease prognosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%